Neutrophil‑ and platelet‑to‑lymphocyte ratios in sepsis: mortality links in diabetic patients and hospital burden in acute kidney injury - Abshori, Nuril F; Iqhrammullah, Muhammad; Mardliyyah, Raihan R; Negara, R Moch S S S; Arif, Achmad Z; Ahdi, Iwal R; Habiburrahman, Muhammad (The Journal of Infection in Developing Countries, 2026)
Introduction: Timely identification of sepsis patients at elevated risk for in-hospital mortality or prolonged hospitalization remains a clinical imperative. This study aimed to assess the prognostic utility of two readily available hematological biomarkers, namely the neutrophil-to-lymphocyte count ratio (NLCR) and platelet-to-lymphocyte count ratio (PLCR), for their association with mortality and length of stay (LOS) among sepsis patients, including high-risk subgroups with acute kidney injury (AKI) or type 2 diabetes mellitus (T2DM). Methodology: This retrospective 1-year cohort study included 202 adult sepsis patients. NLCR and PLCR were derived from admission complete blood counts. Receiver operating characteristic (ROC) curve analysis was used to evaluate discriminative performance, with optimal thresholds determined using Youden’s index. Kaplan–Meier and log-rank tests assessed survival differences, while LOS comparisons were analyzed using Mann–Whitney and Chi-square tests. Results: NLCR demonstrated limited overall prognostic value for mortality (AUC 0.560; sensitivity 53.68%; specificity 63.55%) but showed improved discrimination in patients with T2DM (AUC 0.603). PLCR was not associated with mortality in any subgroup (AUCs: 0.438–0.539). Diabetic patients with low NLCR had significantly higher survival (62.4% vs. 32.8%; p = 0.039). No significant survival differences were observed in the overall or AKI cohorts. Both NLCR and PLCR had poor association with LOS (AUC < 0.55). However, AKI patients with elevated NLCR had significantly prolonged hospitalization (11.5 ± 4.9 vs. 7.83 ± 4.5 days; p = 0.039). PLCR was not significantly associated with LOS. Conclusions: NLCR may provide modest, preliminary prognostic value in specific sepsis subgroups, particularly those with T2DM or AKI, and may serve as a low-cost adjunct for early risk stratification.